Involvement of spinal glutamate in nociceptive behavior induced by intrathecal administration of hemokinin-1 in mice. (23rd March 2016) - Watanabe, Chizuko; Mizoguchi, Hirokazu; Bagetta, Giacinto; Sakurada, Shinobu
Highlights: Hemokinin-1-induced nociceptive behavior was inhibited by NMDA receptor antagonists. Hemokinin-1 produced release of glutamate in the spinal cord. Spinal release of glutamate was inhibited by NMDA receptor antagonists. The release of glutamate may be involved in the nociceptive behavior of hemokinin-1. Abstract: The most recently identified tachykinin, hemokinin-1, was cloned from mouse bone marrow. While several studies indicated that hemokinin-1 is involved in pain and inflammation, the physiological functions of hemokinin-1 are not fully understood. Our previous research demonstrated that the intrathecal (i.t.) administration of hemokinin-1 (0.00625–1.6 nmol) dose-dependently induced nociceptive behaviors, consisting of scratching, biting and licking in mice, which are very similar with the nociceptive behaviors induced by the i.t. administration of substance P. Low-dose (0.0125 nmol) hemokinin-1-induced nociceptive behavior was inhibited by a specific NK1 receptor antagonist; however, high-dose (0.1 nmol) hemokinin-1-induced nociceptive behavior was not affected. In the present study, we found that the nociceptive behaviors induced by hemokinin-1 (0.1 nmol) were inhibited by the i.t. co-administration of MK-801 or D-APV, which are NMDA receptor antagonists. Moreover, we measured glutamate in the extracellular fluid of the mouse spinal cord using microdialysis. The i.t. administration of hemokinin-1 produced a significant increase in glutamate in the spinal cord, which was significantly reduced by co-administration with NMDA receptor antagonists. These results suggest that hemokinin-1-induced nociceptive behaviors may be mediated by the NMDA receptor in the spinal cord.